THE ROLE OF INNATE IMMUNITY RECEPTORS (TLRs) IN MAINTAINING THE HOMEOSTASIS OF THE FEMALE GENITAL TRACT IN DEVELOPING PREGNANCY AND INTRAUTERINE INFECTION - A. V. Karaulov (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
The aim of the present systematic literature review is to summarize data on the role of TLRs in maintaining homeostasis of the female genitals, in maintaining the physiological development of pregnancy, provision of anti-infective resistance in pregnant women with intrauterine infection. The review substantiates the importance of TLRs of female genitals as a necessary and determining factor in the reaction to various changes in the environment, and also responsible for changes in metabolic, structural, or energy, in the maintenance of anti-infective resistance and homeostasis. As universal regulators of vital activity of organism TLRs in conjunction with other receptors of innate immunity provide maintaining the general reactivity and anti-infective resistance at the physiological level. In physiologically developing pregnancy in a background of immunosuppression in response to pregnancy TLRs during contact with infectious and non-infectious pathogens stimulate the production of nonspecific adaptive immunity factors (defensins, cathelicidins, histatines, etc.), which together with the non-specific innate factors lysozyme, complement, properdin, etc. support antiinfective resistance of the female genitals at a high level at the beginning of the infectious process. Possible violations of the development of pregnancy may be accompanied by changes in the response of TLRs to infectious and non-infectious factors until hyper-reaction, excessive inflammation or apoptosis, which requires adequate management of pregnancy. Was established the significance of the influence of pathogens of infectious and noninfectious origin in intrauterine infection indirectly through TLRs in the homeostasis of the organism, on the formation of breaches in anti-infective resistance at the organism and community level the identification of new pathophysiological and immunological pathogenetic mechanisms of development of pathological processes. IUI is a penetration of microorganisms into the tissues of fetus and it’s infection. The inhibition of the functional activity of TLRs is accompanied by the direct effect of the pathogen on the tissues, and during hyper-reaction of TLRs to pathogens revealed a pronounced inflammatory response in the fetus. The level of expression of TLRs correlates directly with the severity of the process that can be considered as early markers of infection. Depending on the nature of the pathogen an increased expression of one or the other TLRs is observed. Explained the lack of symptoms, the possibility of atypical manifestations, the asymptomatic course of infection.